Various Models of Da'wah Approaches in the Qur'an Perspective of Al Qurthubi - Amru Hidayat; Achyar Zein; Junaidi (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
Various models of da'wah approaches are methods or ways used in delivering religious messages. There are several different approaches that are often used in da'wah, each with different objectives and methods. The Qur'an provides many instructions and principles on how to preach effectively. There are a variety of approaches that are often used in da'wah, each with different goals and methods and this is contained in surah An-nahl verse 125. Surah An-Nahl verse 125 of Al-Qurthubi's perspective provides clear guidance on how to do da'wah effectively. Using wisdom, mau'izah hasanah, and good jidal, while still surrendering to Allah's decision, are important principles in the da'wah process. Preachers are expected to deliver messages wisely, prioritize good advice, and argue in a polite manner, all in an effort to achieve the greater goal of da'wah. In this study, the author used a qualitative approach. This method utilizes information, notes, and data from the texts that have been studied. In this method, descriptive analysis is very important, where the author seeks to describe in a structured manner to provide a clear, systematic, objective, and critical explanation and description of the method of delivering messages in Al-Qur'an Surah An-Nahl verse 125 from Al-Qurtubi's perspective.